Surface Modification on Magnesium Alloys’ Hardness and Microstructure Using Friction Stir Processing – A Review - Zuhairah Zulkfli; Zamzuri Hamedon; Nanang Fatchurrohman (Universitas Putra Indonesia YPTK Padang, 2023)
Low density of magnesium-based alloy is one potential as the lightest structural material for light weight-high strength applications for automotive and aerospace. Severe plastic deformation (SPD) together with thermomechanical processing are proved to be a successful method for attaining desired microstructural modifications through achieving fine and highly misoriented microstructures and creating various structures to the bulk properties of magnesium alloy. The material's deformation can result in an altered microstructure that is gainful to the material's requirements. However, the poor deformability of magnesium and its alloys limits the application of the thermomechanical approach. Controlling over temperature and deformation rate is hard to achieve. Among the thermomechanical processes, friction stir processing (FSP) offers an easy way to achieve process stability and mechanical properties enhancement by heat treatment which results in the closure of porosity and refined grain size. During this process, heat is generated by the rotation of the FSP processing tool. Few process parameters such as rotational and traverse speeds should be controlled to make FSP stay within the defined processing condition. It is critical to set the right tool rotational speed as well as traverse speed to ensure adequate heat generation. As there are no established standards for operating the FSP, the only solution is to experiment with different settings to find the best parameter which will produce better quality on processed magnesium alloy workpiece. This paper explores earlier studies on surface modification via FSP technique to improve the mechanical properties strengthening of magnesium alloy mainly on grain size and hardness. The surface modification was done mostly on popular series of magnesium alloy (AZ series) using different tool material, tool geometry and different parameters combination. A comprehensive view of surface modification on magnesium alloys which includes the FSP tool and workpiece material used, variations of FSP parameters settings as well as the effect on hardness and microstructure analysis will be discussed.